Short Term Outcomes of Laparoscopic Complete Mesocolic Excision with Central Vascular Ligation for Right Colonic Cancer (Indian Journal of Public Health Research & Development, 2020)
Background: Laparoscopic complete mesocolic excision with central vascular ligation, when performed inthe right mesocolic plane, produces high quality surgical specimens.Aim of the work: Assessment of feasibility, safety, and quality of surgical specimen after laparoscopiccomplete mesocolic excision with central vascular ligation in right colon.Patients and Method: Fifty patients with right colonic cancer were assigned to receive laparoscopiccomplete mesocolic excision with central vascular ligation during the period from April, 2017 till June,2019 and their data were prospectively collected.Results: The average length of the ileocolic segment was 26.67±2.10 cm,the average distance from nearbowel wall to high vascular tie was 85.26±5.32 mm,the average distance from tumor to high vascular tie was107.82±3.39 mm,and Average number of LN harvest was number 22.72±10.17.Conclusion: Laparoscopic complete mesocolic excision with central vascular ligation procedure isassociated with minimal operative blood loss, rapid recovery after operation, and short hospital stay andadequate number of harvested lymph nodes
Keywords: Outcome, laparoscopic, complete mesocolic.